Species-specific lens activation of the thymidine kinase promoter by a single copy of the mouse alpha A-CRYBP1 site and loss of tissue specificity by multimerization. - Sax, C M (1990)
One copy of the mouse alpha A-crystallin gene alpha A-CRYBP1 site activated the thymidine kinase (tk) promoter in a mouse lens epithelial cell line but not in primary chicken lens cells; multiple copies further activated the tk promoter and extended expression to fibroblasts, B cells, and chicken lens cultures. The loss of lens specificity by multimerization may place selective constraints on the number of alpha A-CRYBP1 sites in the alpha A-crystallin promoter.